Myelitis in systemic lupus erythematosus: clinical characteristics and effect in accrual damage. A single-center experience. (March 2017) - Quintanilla-González, L; Atisha-Fregoso, Y; Llorente, L; Fragoso-Loyo, H
Objective: The purpose of this study was to describe the clinical characteristics of acute transverse myelitis, including the time of their presentation, and to evaluate their effect on accrual damage in patients with systemic lupus erythematosus (SLE). Methods: Patients with SLE who were hospitalized because of incident, noninfectious myelitis at our institute between January 1997 and December 2013 were identified. As a control group, we selected for each of the patients in the study group one SLE patient hospitalized at the closest date to the case due to other severe non-neuropsychiatric (NP) SLE manifestation, with no history of NP manifestations or noninfectious disease. Clinical characteristics, laboratory results, treatment, disease activity (SLEDAI-2K), and damage (SLICC/ACR-DI) were collected from medical charts at the index hospitalization and one year after hospitalization. Results: Demographics and SLE characteristics, including age at SLE diagnosis and time since SLE diagnosis to hospitalization, were comparable in patients with myelitis and controls. At hospitalization, disease activity and cumulative damage were similar in both groups. Patients with myelitis received more aggressive treatment than controls. One year after hospitalization, two of the 15 patients who completed follow-up had symptom improvement without neurologic sequelae, and 13 of them had some improvement of symptoms with neurologic sequelae. Four patients died in the myelitis group, three of them of infectious diseases, and one of alveolar hemorrhage. No patient died because of myelopathy and in the control group no patient died, although three were lost during the follow-up. Disease activity and treatment did not differ between both groups. However, cumulative damage was higher among the patients with myelitis than controls (1.9 ± 0.9 vs 0.75 ± 0.9; p  = 0.003). Conclusion: Patients with myelitis have clinical characteristics similar to those observed in non-NP SLE and receive more aggressive treatment. Furthermore, myelitis is associated with a significant increase in accrual damage compared with severe non-NP manifestations.